Women “Cronistas” in Colonial Latin America - Añón, Valeria (2016)
These archive images bring forth myriad questions about how the past and present are represented. They show the violent intersection of world visions and discursive traditions; translation and survival; dialogue, destruction, and change. It is a storytelling that is individual as well as collective and a space for that which has been expelled or relegated from hegemonic discourse, although this recognition may be limited to a specifi c period, stuck in the quagmire of incessant change. The most critical question that arises here is the following: To whom are we referring when we speak of women cronistas in colonial Latin America? Which types of writing and texts are we indicating? If these texts can be grouped under the broad concept of colonial chronicles , what connections can be made with the predominant colonial literary corpus – a literature directly associated with masculine voices, articulated from the sphere of power and authority? What bonds are established with the actors (soldiers, monks, indigenous nobles, mestizos)? As Julie Greer Johnson has noted, “Because men dominated the writing of both history and literature, the image of women during the colonial period is largely based upon their vision” (157). Nevertheless, Greer Johnson chooses to focus on men’s representation of women. In contrast, this chapter reveals how women represent, write, speak, remember, and affi rm themselves and make requests in the complex sphere of the early Latin American colonial world.